Single-site versus multi-port retroperitoneoscopic adrenalectomy for benign adrenal tumors: a comparative clinical and economic analysis - Wu Wensong; Fang Dengpan; Xu Jianxin; Wang Yiwei; Chen Fangmin (BMC Urology, 2026)
Abstract Background Laparoendoscopic single-site retroperitoneoscopic adrenalectomy (LESS-RA) has emerged as a further refinement of minimally invasive adrenal surgery. However, comparative data on perioperative outcomes and direct economic value relative to conventional retroperitoneoscopic laparoscopic adrenalectomy (RLA) remain limited, particularly within the Chinese healthcare setting. Methods We retrospectively analyzed 65 consecutive patients who underwent LESS-RA ( n = 29) or RLA ( n = 36) for solitary benign adrenal tumors (maximum diameter ≤ 4 cm) at two centers between June 2022 and May 2025. Perioperative outcomes, cosmetic results assessed by the Vancouver Scar Scale (VSS), postoperative complications graded by the Clavien-Dindo classification, and Consumer Price Index-adjusted hospitalization costs were compared. A cost-effectiveness analysis was performed using the incremental cost-effectiveness ratio (ICER). Results All 65 procedures were completed laparoscopically without open conversion. Operative time, intraoperative blood loss, adrenal dissection time, postoperative pain scores, time to ambulation, diet resumption, and drainage duration were comparable between groups. The LESS-RA group demonstrated significantly shorter incision length (2.8 vs. 5.0 cm; P < 0.01), lower VSS scores (4 vs. 6; P = 0.011), and shorter hospital stay (5 vs. 7 days; P = 0.027). Complication rates did not differ significantly (Clavien-Dindo Grade I: 3.4% vs. 5.6%; P = 0.71). Adjusted total hospitalization cost was significantly lower in the LESS-RA group (18,255 vs. 21,080 RMB; P < 0.01), driven by savings in hospitalization bed fees and medications. ICER analysis confirmed LESS-RA as an economically dominant strategy. Conclusions LESS-RA is safe, effective, and comparable to RLA perioperatively. By providing superior aesthetic outcomes and significant cost savings, LESS-RA represents an optimal, cost-effective surgical option perfectly aligned with the principles of value-based healthcare.